A Robust Adaptive Tracking Controller for an Aircraft With Uncertain Dynamical Terms - Tanyer, İlker; Tatlıcıoğlu, Enver; Tatlıcıoğlu, Enver; Zergeroğlu, Erkan (Elsevier Ltd., 2014)
This work presents, the design and the corresponding analysis of a nonlinear controller for an aircraft system subject to uncertainties in the dynamics and additive state-dependent nonlinear disturbance-like terms. Specifically; dynamic inversion technique in conjunction with a robust integral of the signum of the error feedback and an adaptive term is utilized in the overall controller design. Lyapunov based stability analysis techniques are then utilized to prove global asymptotic convergence of the tracking error. © IFAC.
19th IFAC World Congress on International Federation of Automatic Control, IFAC 2014; Cape Town; South Africa; 24 August 2014 through 29 August 2014
Keywords: Robust control; Uncertain dynamic systems; Aircrafts; Asymptotic stability; Controllers